2020
DOI: 10.1159/000508564
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Chromosome Y and Its Potential Applications as Biomarker in Health and Forensic Sciences

Abstract: necessity to clarify the molecular mechanism behind its occurrence and its possible applications in both health and forensic studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 94 publications
(202 reference statements)
0
14
0
Order By: Relevance
“…The lack of a reduced incidence of GVHD in this study might be explained by the tissue distribution of Del(Y). Generally, Del(Y) is considered to present mainly in blood cells, and most studies on Del(Y) used blood samples 12,13 . Since there is limited information on Del(Y) in peripheral tissues other than blood cells, donor cells are likely to be sensitized by H-Y antigens and Del(Y) might have only limited impact on the incidence of GVHD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of a reduced incidence of GVHD in this study might be explained by the tissue distribution of Del(Y). Generally, Del(Y) is considered to present mainly in blood cells, and most studies on Del(Y) used blood samples 12,13 . Since there is limited information on Del(Y) in peripheral tissues other than blood cells, donor cells are likely to be sensitized by H-Y antigens and Del(Y) might have only limited impact on the incidence of GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, del(Y) is considered to present mainly in blood cells, and most studies on del(Y) have used blood samples. 12,13 Because there is limited information on del(Y) in peripheral tissues other than blood cells, donor cells are likely to be sensitized by H-Y antigens, and del(Y) might have only a limited impact on the incidence of GVHD. However, several studies have reported that del(Y) was found in tissues besides blood cells, such as buccal mucosa and brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are forms of aneuploidy that generate combinations other than XX or XY, and genetic variants can mediate reproductive development in diverse ways, as in androgen insensitivity syndrome, XX male syndrome (de la Chapelle syndrome), congenital adrenal hyperplasia, and persistent Mullerian duct syndrome, among others. Further, loss of the Y chromosome in a proportion of cells is a known occurrence with age in otherwise healthy males [ 15 ]), and many of these traits vary within the same individual across the lifespan.…”
Section: Sex and Gendermentioning
confidence: 99%
“…LOY can be quantified either using classical molecular cytogenetics [3] or genomics data (for instance, Whole Genome Sequencing/WGS data or the mean intensity log-R ratio (mLRR) OF micro-array probes) [6]. Several formulas have been proposed to translate mLRR into LOY(%).…”
Section: To the Editormentioning
confidence: 99%